Perception, utilization, and challenges of point-of-care testing among healthcare workers: A cross-sectional study - Seema Patel; Preeti Chauhan; Aliya Arshad; Ruby Khan; Pratip Jana; Dakshita Chauhan (Asian Journal of Medical Sciences, 2026)
Background: Point-of-care testing (POCT) is an important diagnostic approach that enables rapid clinical decision-making and supports patient-centered care across healthcare settings. Aims and Objectives: The present study aimed to evaluate the perception, utilization, benefits, and challenges of POCT among healthcare workers. Materials and Methods: A cross-sectional survey was conducted among healthcare professionals in various clinical settings. The questionnaire assessed usage patterns, perceived clinical utility, training practices, and quality assurance measures related to POCT. Results: POCT was widely used, particularly in intensive care units and emergency departments, with increasing adoption in outpatient settings. Most respondents agreed that POCT reduces turnaround time (90%), enables rapid clinical decision-making (83%), and improves patient monitoring (100%). In addition, 95% reported improved patient outcomes, and 94% observed reduced hospital stays. A majority (88%) perceived POCT as cost-effective, and all participants recommended its broader implementation. However, challenges were identified, including operator dependency, sample quality issues, and difficulties in documentation and data integration. Variability in training practices and limited awareness of accreditation standards were also noted, despite the presence of internal quality control measures and standard operating procedures in many settings. Conclusion: POCT is widely perceived as a valuable diagnostic tool that enhances efficiency and patient care. Addressing gaps in training, quality assurance, accreditation, and data management are essential to ensure accurate, reliable, and standardized implementation.